Algal toxins : nature, occurrence, effect and detection - Evangelista, Valtere (Springer, 2017)
The World of Algae -- Cyanobacterial Diversity in Relation to the Environment -- Toxicity of Fresh Water Algal Toxins to Humans and Animals...